Labor Union Strength and the Equality of Political Representation. Issue 4 (5th December 2016) - Flavin, Patrick
Abstract : Amid growing evidence of 'unequal democracy' in the United States, labor unions can play a potentially important role by ensuring that low-income citizens' opinions receive more equal consideration when elected officials make policy decisions. To investigate this possibility, this article evaluates the relationship between labor union strength and representational equality across states and finds evidence that states with higher levels of union membership weigh citizens' opinions more equally in the policy-making process. In contrast, there is no relationship between the volume of labor union contributions to political campaigns in a state and the equality of its political representation. These findings suggest that labor unions promote greater political equality primarily by mobilizing their working-class members to political action and, more broadly, underscore the important role that organized labor continues to play in shaping the distribution of political power across American society.